2014
DOI: 10.1093/jxb/eru024
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope discrimination during branch photosynthesis of Fagus sylvatica: field measurements using laser spectrometry

Abstract: On-line measurements of photosynthetic carbon isotope discrimination ((13)Δ) under field conditions are sparse. Hence, experimental verification of the natural variability of instantaneous (13)Δ is scarce, although (13)Δ is, explicitly and implicitly, used from leaf to global scales for inferring photosynthetic characteristics. This work presents the first on-line field measurements of (13)Δ of Fagus sylvatica branches, at hourly resolution, using three open branch bags and a laser spectrometer for CO₂ isotopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 68 publications
2
12
1
Order By: Relevance
“…Furthermore, it assumes (3) that the effect of decreasing transpiration on R wt,int due to defoliation leads to an underestimation of R wt , and therefore F wt and its isotope-related effect on 13 C l , because both stem photosynthesis [26] as well as CO 2 efflux rates [27] are positively related to sap flow (but see [11] for confounding effects). However, despite this potential underestimation, our modelled R wt rates for foliated beech of the first experimental phase were in the range of CO 2 efflux rates previously reported for (foliated) beech [3,8], demonstrating the validity of using the model also for foliated trees during the light.…”
Section: Modelling R Wtsupporting
confidence: 73%
See 3 more Smart Citations
“…Furthermore, it assumes (3) that the effect of decreasing transpiration on R wt,int due to defoliation leads to an underestimation of R wt , and therefore F wt and its isotope-related effect on 13 C l , because both stem photosynthesis [26] as well as CO 2 efflux rates [27] are positively related to sap flow (but see [11] for confounding effects). However, despite this potential underestimation, our modelled R wt rates for foliated beech of the first experimental phase were in the range of CO 2 efflux rates previously reported for (foliated) beech [3,8], demonstrating the validity of using the model also for foliated trees during the light.…”
Section: Modelling R Wtsupporting
confidence: 73%
“…These δ 13 C values were more negative than reported in other studies for beech ( − 22 ‰ to − 26 ‰; [28,29]), most probably due to the low light conditions in the climate chambers (maximum values around 600 µmol photons m −2 s −1 ), which increase photosynthetic carbon isotope discrimination and thus lead to more negative δ 13 [3,15]. More important than the absolute δ 13 C values of woody tissue net CO 2 efflux is the associated isotope discrimination 13 C R wt , as any F wt only affects (and potentially biases) leaf 13 C apparent , when it is associated with a noticeable 13 C fractionation.…”
Section: C Discrimination Associated With R Wt ( 13 R Wt )contrasting
confidence: 60%
See 2 more Smart Citations
“…These measurable changes in the carbon isotope composition of soil and ecosystem respired CO 2 were detected using discrete instead of continuous isotope measurements. However, first in situ real-time measurements revealed that such conclusions are not that straightforward as Δ 13 C displays diurnals changes (Gentsch et al, 2014) which are not always reflected in the carbon isotope signature of SR, especially under wet conditions (Wingate et al, 2010). …”
Section: Introductionmentioning
confidence: 99%